Acculturation and Occupational Shift among the Badi Community of Surkhet - Shahi, Bhupendra Bahadur (Journal of Tikapur Multiple Campus, 2026)
This paper assesses the influence of acculturation practices on the occupational shift of Badi community in Surkhet having the major objective of exploring better social adjustment. The study employs exploratory sequential design based on mixed method (QUAN-QUAL). In essence to explore the livelihoods of Badi, they were found engaged in entertainment occupations singing and dancing, relying on upper caste patronage and living in their homes. Their socio-economic conditions were measurable marked by dependency and discrimination. However, after democracy in 1991, the Badi people are found be acculturate in terms of occupation freedom, pursue education, and occupations diversification. Despite facing challenges during the Maoist conflict (1995-2005), this period became pivotal in fostering their desire for independence; they realized “Aba Magi Khane Hoina Gari Khane Ho” (work independently for survival not to be dependent) and opportunities and rights have to grab against not to accept. Thus, the research explores that acculturation practices have contributed to their occupational shift towards agriculture and other. However, the Badi community still found facing socio-economic and cultural challenges; lagging behind other castes in terms of livelihood improvement in Surkhet.